(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, the endogenous characteristics of political thinking, the influence of political thinking on the development of a democratic society, the possibilities of the influence of endogenous characteristics of political thinking on the development of a democratic society, and the social significance of the influence of the endogenous characteristics of political thinking on the development of a democratic society are studied.